ChemInform Abstract: Access to Isoquinolines and Isoquinolin‐3‐ols via Rh(III)‐Catalyzed Coupling/Cyclization Cascade Reaction of Arylimidates and Diazo Compounds. Issue 38 (September 2016) - Li, Xing Guang; Sun, Min; Jin, Qiao; Liu, Kai; Liu, Pei Nian
Abstract: An oxidant‐free, Rh(III)‐catalyzed coupling/cyclization cascade reaction yielding isoquinolines via C—H activation is developed.